Retorika I Dewa Made Rai Mesi dalam Pertunjukan Wayang Kulit Purwa Lakon Irawan Rabi - I Putu Ardiyasa (Institut Seni Indonesia Yogyakarta, 2018)
Rai Mesi is an interesting phenomenon in the world of puppetry in Bali because its presence offers a different color and is able to revive the wayang kulit purwa. It is also what makes it a legendary dalang for the people. Rai Mesi as a dalang who is good at bringing stories, always be the first choice for people who want to hold a puppet show. Each show is always packed with spectators. It is therefore not surprising that the style of Rai Mesi puppetry is still used as a reference by the young puppeteers until now. Given its capacity as the mastermind of the story, the focus of the discussion in this paper is the issue of rhetoric that focuses on the choice of words, the use of language, and the way of narration, both in narrative and in dialogue. The data used is Lakon Irawan Rabi in the form of ribbon tape recordings which are then transcribed into written form. The result of the research shows that Rai Mesi has succeeded in composing the Irawan Rabi play as a Javanese wayang kulit playwoman to play Balinese parrot leather puppets through the processing of language style, bothbeautiful language, hilarious, figurative, and alternation. In addition to processing the style of language, Rai Mesi in his speech also inserted the language outside Bali, be it the language of the archipelago and foreign languages. Rai Mesi’s rhetoric is very communicative.Rai Mesi merupakan fenomena yang menarik dalam dunia pedalangan di Bali karena kehadirannya menawarkan warna yang berbeda dan mampu menggairahkan kembali pertunjukan wayang kulit purwa. Hal ini pula yang membuatnya menjadi dalang legendaris bagi masyarakatnya. Rai Mesi sebagai dalang yang pandai membawakan cerita, selalu menjadi pilihan pertama bagi masyarakat yang ingin menyelenggarakan pertunjukan wayang. Setiap pertunjukkannya selalu dipadati penonton. Oleh karenaitu tidak mengherankan apabila gaya pedalangan Rai Mesi masih dijadikan acuan oleh dalang-dalang muda hingga sekarang. Mengingat kapasitasnya sebagai dalang cerita, maka fokus bahasan dalam tulisan ini adalah masalah retorika yang berfokus pada pemilihan kata, pemakaian bahasa, serta cara penuturannya, baik dalam narasi maupun dialognya. Data yang digunakan adalah Lakon Irawan Rabi dalam bentukrekaman kaset pita yang kemudian ditranskrip ke dalam bentuk tulisan. Hasil penelitian menunjukkan bahwa Rai Mesi telah berhasil menggubah Lakon Irawan Rabi sebagai lakon wayang kulit Jawa menjadi lakon carangan wayang kulit parwa Bali melalui pengolahan gaya bahasa, baik bahasa indah, kocak, kiasan, dan alternasi. Selain mengolah gaya bahasa, Rai Mesi dalam tuturannya juga menyisipkan bahasa luar Bali, baik itu bahasa Nusantara maupun bahasa asing. Retorika Rai Mesi sangat komunikatif.